Synthesis of Highly Cis, Syndiotactic ROMP Polymers Using Ruthenium Metathesis Catalysts - Rosebrugh, Lauren E. (2013)
The first example of ruthenium-mediated ring-opening metathesis polymerization (ROMP) generating highly cis, highly tactic polymers is reported. While the cis content varied from 62 to >95% depending on the monomer structure, many of the polymers synthesized displayed high tacticity (>95%). Polymerization of an enantiomerically pure 2,3-dicarboalkoxynorbornadiene revealed a syndiotactic microstructure.